Entrepreneurship and economic growth: An investigation into the relationship between entrpreneurship and total factor productivity growth in the EU - Andrzej P. Dabkowski (Center for Social and Economic Research (CASE), 2011)
Endogenous growth theory assigns an important role for entrepreneurship in the process of economic development. This paper sets to formally test the impact of entrepreneurship on economic growth. Entrepreneurship is represented by a number of proxy variables, whereas Total Factor Productivity is used as a measure of economic growth. Panel data of 26 European countries repeatedly sampled over a period of 11 years is used to estimate a Random Effects model. This study finds that entrepreneurship contributes to growth moderately. It is not, nonetheless, a dominant force shaping changes in TFP growth rates. Business Birth Rate, Self-employment Rate, Business Investment and Labour Productivity Growth were all found to be highly significant. The article concludes that more encompassing measure of entrepreneurship needs to be developed, one that would reflect the complexity of the notion.
Keywords: O11; O30; O47; O52; L26; 330; entrepreneurship; total factor productivity; economic growth; the EU; Entrepreneurship-Ansatz; Wirtschaftswachstum; Produktivität; EU-Staaten